REVERBERATION UNDER ARCTIC ICE - Brown, J. R. (1963)
Reverberations from detonators exploded under Arctic ice were recorded in the octave bands 1.28-2.56 and 5.12-10.24 kc/sec. The measurements were made from a polar floe during 4-6 September 1963 in Prince Regent Inlet near 73 degrees N and 91 degrees W. The resultant scattering strengths were similar to those obtained by Chapman and Harris from recordings of reverberations made in the open sea in 30-knot winds. (Author)